1988
DOI: 10.1063/1.99024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium sulfide treatment on band bending in GaAs

Abstract: Recent evidence suggests that sodium sulfide treatment of GaAs surfaces results in the reduction of surface recombination and in Fermi level unpinning. We have used a surface conductivity technique to measure the Fermi level position of samples with and without sodium sulfide treatment. This method has specific advantages over spectroscopic techniques for studying thin films on GaAs. Photoluminescence (PL) measurements were used to qualitatively evaluate surface recombination. We conclude that while the reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 5 publications
1
30
0
Order By: Relevance
“…Initial work involving chemical treatments focused on GaAs surfaces passivated with inorganic sulfides, such as Na 2 S and (NH 4 ͒ 2 S. [1][2][3][4][5][6] More recently, passivation has been successfully achieved with the use of selenium sulfide 7 and other group VI sources. [8][9][10] The success of these inorganic sulfides has led some workers to investigate organic thiols, 11 most notably octadecylthiol ͑ODT͒, which forms a selfassembled monolayer on the surface of GaAs.…”
Section: Department Of Chemistry and Materials Research Laboratory Umentioning
confidence: 99%
“…Initial work involving chemical treatments focused on GaAs surfaces passivated with inorganic sulfides, such as Na 2 S and (NH 4 ͒ 2 S. [1][2][3][4][5][6] More recently, passivation has been successfully achieved with the use of selenium sulfide 7 and other group VI sources. [8][9][10] The success of these inorganic sulfides has led some workers to investigate organic thiols, 11 most notably octadecylthiol ͑ODT͒, which forms a selfassembled monolayer on the surface of GaAs.…”
Section: Department Of Chemistry and Materials Research Laboratory Umentioning
confidence: 99%
“…The sulfur-oxygen stretching vibration of sulfate, SO 4 2 -and sulfite, SO 3 2 -ions occur in the region of 1140-1170 cm-1 and 950-1000 cm-1 , respectively, while those of a thiosulfate ion, S2032-, occurs in the regions of 1050-1150 cm"1 and 950-1050 cm-1 [33,34]. It is likely that the broad bands observed in these regions in the spectra resulted from a combination of these sulfur-oxygen containing compounds on the surface.…”
Section: Infrared Resultsmentioning
confidence: 99%
“…The sulfides used in the treatments includes gases, such as H 2 S, and liquids, such as Na 2 S.9H 2 0 and (NH 4 ) 2 S solutions. These treatments have been shown to result in improvement in the GaAs surface electronic properties, including low surface recombination velocity [11, low surface state density [2,3], and Fermi level shifting or unpinning [4][5][6]. In addition, enhanced performance in heterojunction bipolar transistors (HBTs) [7,81, metal-insulator-semiconductor (MIS) structures [91, solar cells [6,10], laser diodes [11,12], and p-n junction diodes [3] have all been observed.…”
Section: Introductionmentioning
confidence: 99%
“…For N-face n-GaN, the exact reason why the sulfide passivation causes the surface Fermi level to shift toward the conductionband edge is not clear at this moment. Offsey et al, 23 investigating the surface characteristics of sulfur-passivated ͑001͒ n-GaAs by photochemistry, and Besser and Helms, 24 investigating the effect of sulfide treatment on the band-bending behaviors of GaAs:Si by PL, reported that the treatments resulted in the unpinning of the surface Fermi level by reducing the surface state density, leading to a reduction of the band bending. Thus, the surface Fermi-level shift observed in our passivated sample might also be explained in terms of the reduction in the surface state density, reducing the band-bending and so the surface barrier heights.…”
Section: H276mentioning
confidence: 98%